Indoor positioning: technology comparison analysis - Md Din, Marina; Jamil, Norziana; Maniam, Jacentha; Afendee Mohamed, Mohamad (International Journal of Engineering and Technology, 2018)
A system that allows users to find and track a specific position is known as positioning system. Global Positioning System (GPS) is one of top known position tracking system that commonly used to find position and location of object outdoor. Tracking an object indoor using GPS is not highly recommended because the signals transmitted through a satellite to a device indoor gets blocked and resulted in weak signals. Thus, an indoor positioning system (IPS) that tracks and positions object indoor has been implemented to overcome the issues of signals multipath that resulted from GPS. The aim of this paper is to provide up to date indoor positioning technologies and compares the technologies according to its technical perspectives.Â Â